Edukasi mengenai Obat Nyeri terhadap Pasien Rawat Jalan di RSUD KHZ. Musthafa, Kabupaten Tasikmalaya - Saeful Amin; Meisye Utami Dianingsih; Henny N (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This study aims to evaluate the effectiveness of education on the use of pain medication for outpatients at KHZ Musthafa Regional Hospital, Tasikmalaya Regency. Using a qualitative descriptive approach, this study describes in depth the counseling process carried out by pharmacists through the delivery of materials and interactive question and answer sessions. The education provided includes types of pain medication, rules of use, side effects, drug interactions, and the importance of stomach medication as a companion therapy. Data were collected through direct observation and documentation of interactions during counseling activities. Analysis was carried out using thematic methods to identify patterns of patient understanding and response. The results showed that direct and communicative education can improve patient understanding of pain medication, encourage adherence to therapy, and contribute to improving patient quality of life. These findings emphasize the importance of the active role of pharmacists in providing accurate and easy-to-understand drug information as an integral part of holistic health services that are oriented towards patient safety.